3D-templated, fully automated microfluidic input/output multiplexer for endocrine tissue culture and secretion sampling. Issue 2 (19th December 2016) - Li, Xiangpeng; Brooks, Jessica C.; Hu, Juan; Ford, Katarena I.; Easley, Christopher J.
Abstract : An automated 16-channel microfluidic multiplexer (μMUX) was developed for dynamic stimulation and interrogation of islets and adipose tissue. Abstract : A fully automated, 16-channel microfluidic input/output multiplexer (μMUX) has been developed for interfacing to primary cells and to improve understanding of the dynamics of endocrine tissue function. The device utilizes pressure driven push-up valves for precise manipulation of nutrient input and hormone output dynamics, allowing time resolved interrogation of the cells. The ability to alternate any of the 16 channels from input to output, and vice versa, provides for high experimental flexibility without the need to alter microchannel designs. 3D-printed interface templates were custom designed to sculpt the above-channel polydimethylsiloxane (PDMS) in microdevices, creating millimeter scale reservoirs and confinement chambers to interface primary murine islets and adipose tissue explants to the μMUX sampling channels. This μMUX device and control system was first programmed for dynamic studies of pancreatic islet function to collect ∼90 minute insulin secretion profiles from groups of ∼10 islets. The automated system was also operated in temporal stimulation and cell imaging mode. Adipose tissue explants were exposed to a temporal mimic of post-prandial insulin and glucose levels, while simultaneous switching between labeled and unlabeled free fatty acid permitted fluorescent imaging of fatty acid uptake dynamics in real time over a ∼2.5 hour period. Application with varying stimulation and sampling modes on multiple murine tissue types highlights the inherent flexibility of this novel, 3D-templated μMUX device. The tissue culture reservoirs and μMUX control components presented herein should be adaptable as individual modules in other microfluidic systems, such as organ-on-a-chip devices, and should be translatable to different tissues such as liver, heart, skeletal muscle, and others.